MEDICAL TERMINATION OF PREGNANCY- AN OVERVIEW - MAJOR (DR) V K YADAV,MD; DR. PARAG SHARMA,MD (International Journal of Pharma and Bio Sciences, 2013)
Medical Termination of Pregnancy (MTP) is indicated under the conditions as laid down in the MTP act 1971 of India. MTP act ensures the correct intervention depending upon the stage of unwanted pregnancy thereby minimizing the chance of illegal abortions which is the reason for higher mortality and morbidity in India. Available methods are Medical in the early pregnancies and surgical comprising of Dilatation and curettage in late pregnancies. However MTP Act 1971, permits abortions only up to 20 weeks of the pregnancy. This review discusses the current methods of Medical abortions available in India.